Secondary Effects of Glyphosate Action in Phelipanche aegyptiaca: Inhibition of Solute Transport from the Host Plant to the Parasite - Shilo, Tal; Rubin, Baruch; Plakhine, Dina; Gal, Shira; Amir, Rachel; Hacham, Yael; Wolf, Shmuel; Eizenberg, Hanan (Frontiers in Plant Science, 2017)
It is currently held that glyphosate efficiently controls the obligate holoparasite Phelipanche aegyptiaca (Egyptian broomrape) by inhibiting its endogenous shikimate pathway, thereby causing a deficiency in aromatic amino acids (AAA). While there is no argument regarding the shikimate pathway being the primary site of the herbicide’s action, the fact that the parasite receives a constant supply of nutrients, including proteins and amino acids, from the host does not fit with an AAA deficiency. This apparent contradiction implies that glyphosate mechanism of action in P. aegyptiaca is probably more complex and does not end with the inhibition of the AAA biosynthetic pathway alone. A possible explanation would lie in a limitation of the translocation of solutes from the host as a secondary effect. We examined the following hypotheses: a) glyphosate does not affects P. aegyptiaca during its independent phase and b) glyphosate has a secondary effect on the ability of P. aegyptiaca to attract nutrients, limiting the translocation to the parasite. By using a glyphosate-resistant host plant expressing the “phloem-mobile” green fluorescent protein (GFP), it was shown that glyphosate interacts specifically with P. aegyptiaca, initiating a deceleration of GFP translocation to the parasite within 24 h of treatment. Additionally, changes in the entire sugars profile (together with that of other metabolites) of P. aegyptiaca were induced by glyphosate. In addition, glyphosate did not impair germination or seedling development of P. aegyptiaca but begun to exert its action only after the parasite has established a connection to the host vascular system and became exposed to the herbicide. Our findings thus indicate that glyphosate does indeed have a secondary effect in P. aegyptiaca, probably as a consequence of its primary target inhibition—via inhibition of the translocation of phloem-mobile solutes to the parasite, as was simulated by the mobile GFP. The observed disruption in the metabolism of major sugars that are abundant in P. aegyptiaca within 48 h after glyphosate treatment provides a possible explanation for this inhibition of translocation and might reflect a critical secondary effect of the herbicide's primary action that results in loss of the parasite’s superior sink for solutes.